Keanekaragaman Mamalia di Cagar Alam Rimbo Panti, Kabupaten Pasaman, Sumatera Barat - Tomi Kasayev; Jabang Nurdin; Wilson Novarino (Universitas Andalas, 2018)
Rimbo Panti Nature Reserve is a conservation area located in West Sumatra which consisted of two main habitat types, dry hilly and swampy forest habitat types. These forest types potentially board many species of mammals. This research was conducted from December 2015 to March 2016 in The Nature Reserve to determine the diversity of mammals occupied each type of habitats. Twenty two camera traps were installed in pairs, six pairs in the dry hilly habitat (574-871 m asl) and five pairs in the swampy habitat (216-261 m asl). From a total 109 photos, 17 species were identified, consisted of 11 species from hilly and 10 species from swampy forest habitat. There were four species found in both habitat types. Shannon-Wiener diversity index showed that mammalian diversity of Rimbo Panti Nature Reserve is moderate (H’=1.95) while mammalian diversity in swampy forest (H’= 2.06) was higher than hilly habitat forest (H’=1.54).